The Changes of Plasma Homocysteine and Lipoprotein (a) Levels in Patients With Unstable Angina - Şahin, Şemsettin; İlhan, Necip; Seçkin, Dilara; İlkay, Erdoğan (Fırat University, 2002)
Aim: The aim of this study was to investigate the change of plasma Lipoprotein (a) and homocysteine levels in patients with unstable angina. Material Method: This study was done on patients who pre-diagnosed as unstable angina pectoris (UA) in Firat Medical Center, Clinic of Cardiology. Thirty one patients were included in this study and following first beginning of angina the blood samples were taken for homocysteine and lipoprotein (a) levels and these parameters were compared with control group. Results: As a conclusion the homocysteine (UA: 36,72 ± 13,60 K: 12,63 ± 3,65 µmol/L) and Lp (a) (UA: 44,81±20,24, K: 19,53 ± 7,88 mg/dL) levels were found statistically significant higher than control group (p

Amaç: Bu çalışmanın amacı anstabil anjinalı hastalarda plazma Lipoprotein (a) ve Homosistein düzeylerinin değişimini incelemektir. Gereç ve Yöntem: Bu çalışma Fırat Tıp Merkezi Kardiyoloji Kliniğinde Anstabil anjina (UA) ön tanısı almış hastalar üzerinde yapılmıştır. Çalışmada 31 hasta değerlendirmeye alınmış olup, bu hastalardan ilk göğüs ağrısının başlamasını takiben alınan kan örneklerinde, homosistein ve lipoprotein (a) düzeyleri tayin edilerek kontrol grubuna göre karşılaştırılmıştır. Bulgular: Sonuçlar incelendiğinde, Homosistein (UA: 36,72 ± 13,60 K: 12,63 ± 3,65 µmol/L) ve Lp(a) düzeyleri (UA: 44,81±20,24; K: 19,53 ± 7,88 mg/dL) anstabil anjinalı hastalarda kontrol grubuna göre anlamlı olarak yüksek bulunmuştur (p
ANSTABİL ANJİNALI HASTALARDA PLAZMA HOMOSİSTEİN VE LİPOPROTEİN (a) DÜZEYLERİNİN DEĞİŞİMİ